ANALYSIS OF THE INFLUENCE OF GEOLOGICAL FACTORS ON THE DEPTH OF THE FILTRATE INVADED ZONE AT THE PRIMARY DISCLOSURE OF GRANULAR RESERVOIRS ACCORDING TO THE WELL-LOGGING DATA - Karpenko, O.; Sobol, B.; Myrontsov, Myrontsov; Karpenko, Karpenko (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Possibilities of using the well-logging data for revealing the factors of the geological nature that influence the formation of invaded zone of a drilling mud filtrate at oil and gas wells drilling are considered. Electrical logging data were used with probes of different sizes and different types for adequate calculation of the relative diameter of the invaded zone. 5 wells from the gas condensate field were selected for analysis. The terrigenous section of the wells is represented by the alternation of argillites, siltstones and sandstones. Rocks reservoirs of granular type; the layers with thicknesses from 3,4 to 18,2 m were selected for analysis. The results of statistical analysis (cluster and factor analyzes) revealed 3 groups of rocks, the characteristic features of which are significantly different from the invaded zone, layer thickness and porosity and gas saturation coefficients. It is established that for terrigenous sections with reservoir rocks of granular type (Serpukhovian) for one field on the example of 5 wells there is a maximum direct correlation between the value of the relative diameter of the invaded zone and the thickness of the layers. The conducted researches allow making prognostic estimations concerning the approximate distributions of diameters of an invaded zone in terrigenous cuts in case of accident-free drilling with observance of technological conditions.
Keywords: reservoir rock; well logging; invaded zone; cluster analysis; relative diameter; electrical resistivity; porosity coefficient